The effects of nanotopography and coculture systems to promote angiogenesis for wound repair - Kim, Tae Hee; Kim, Soo Hyun; Jung, Youngmee (FUTURE MEDICINE LTD, 2016)
Insufficient angiogenesis in severe wounds delays wound repair because of a lack of blood supply to the wound site. Therefore, pro-angiogenic therapeutics may enhance wound repair. Many studies have investigated various physical and biochemical cues to improve angiogenesis, such as biocompatible materials, surface modifications, angiogenic factors and coculture systems using various cell types. However, the present capability to mimic the micro-and nanostructure of the natural microenvironment, particularly its porous, fibrous features, is limited. Nanotopography may represent a promising tool to overcome these limitations. Here, we discuss various approaches to the use of nanotopography to enhance angiogenesis and consider the combination of coculture systems with nanotopography to mimic the native environment for promotion of angiogenesis in wound healing and repair.
Keywords: SMOOTH-MUSCLE-CELLS; ACID MICRO-PATTERN; ENDOTHELIAL-CELLS; EXTRACELLULAR-MATRIX; TUBE FORMATION; LOW-DENSITY; PERICYTES; MECHANISMS; NANOSCALE; ADHESION